ITS-based wireless traffic monitoring solution - Natalja Osintsev; Victoria Nozick (Big Data and Computing Visions)
In recent times, we have witnessed an extraordinary surge in technological advancements. The rise in transportation, driven by various factors such as schools, offices, factories, and more, has become increasingly apparent. The extensive use of personal vehicles contributes significantly to the escalation of transportation demands, resulting in pollution and a rapid surge in traffic congestion, especially in urban areas. To curb this issue, it is imperative to implement effective techniques. This paper explores the contemporary approach to traffic monitoring systems and highlights the indispensable role of wireless sensor networks in addressing these challenges.